Management of Unresectable Cholangiocarcinoma Using Modern Radiation Therapy Techniques - Demircioglu, Deniz; Moreno, Lou-Anne Acevedo; Hall, William A. (Digestive Disease Interventions, 2024)
Cholangiocarcinoma (CCA) is a malignancy of epithelial cells in the bile duct, categorized based on its anatomical location as intrahepatic, perihilar, or extrahepatic. It has a low prevalence of ∼1.6 cases per 100,000 people in the United States, but has a poor prognosis. All stages included, CCA has a 5-year survival rate of less than 10%. The preferred curative treatment for intrahepatic, perihilar, and extrahepatic CCA is surgical resection combined with systemic chemotherapy. However, resection is not always a viable option for many patients, as the disease is often discovered at the time of diagnosis to be either metastatic or locally advanced precluding surgical resection. In this setting, a variety of options can be used, one of which is radiation therapy (RT). The administration of RT has evolved tremendously over the past decades. Total doses given can be limited by a tumor's proximity to regional normal organs such as the liver, stomach, bile duct, and small and large bowel. When a CCA is unresectable, it is often in close proximity to radiosensitive organs. Delivering RT in this setting therefore requires precise delivery techniques. An emerging technique known broadly as stereotactic body radiation therapy (SBRT) or stereotactic ablative body radiation therapy gives a highly focused, often ablative, form of RT to a defined and specific target. Categorically, SBRT offers a quick and efficient management option, in some cases only one to three total treatments. This narrative reviews various applications of SBRT for cholangiocarcinoma including SBRT alone, SBRT with chemotherapy, SBRT with chemotherapy followed by a liver transplantation (orthotopic liver transplantation), and finally novel combinations of SBRT with immunotherapy.
Keywords: stereotactic body radiation therapy; cholangiocarcinoma; SABR therapy